The Role of External Auditing in Evaluating University Performance Using the Malcolm Baldrige Model for Total Quality Management: An Applied Study on a Sample of Public Universities in Iraq - Al-Laban, Dhyaa Abdulrazaq Abduljabar; Dhibi, Mohamed (Journal of Ecohumanism, 2024)
This research aims to study the role of external auditing in evaluating university performance by applying the Malcolm Baldrige model within public higher education institutions in Iraq. The research was conducted on five public universities in Iraq: Basra, ThiQar, Al-Muthanna, Wasit, and Diyala universities. The study delves into the impact of external auditing on university performance evaluation based on the theory of total quality management. This study uniquely combines external auditing as an independent variable and university performance outcomes as a dependent variable within the Malcolm Baldrige model for total quality management, applied specifically to Iraqi universities. This approach highlights a focus on improving institutional and academic performance through a comprehensive and modern model. Additionally, it sheds light on the role of external auditing in promoting transparency, accountability, and achieving universities’ strategic objectives. The variable "performance outcomes" was selected with the consensus of expert referees due to its relevance to the application domain in the study population.Data were collected using a specially designed questionnaire, and the study found a significant relationship between external auditing and performance outcomes. The main findings revealed a lack of awareness among responsible entities about the importance of using the Malcolm Baldrige model to evaluate universities’ strategic performance outcomes. Furthermore, it showed that external auditing plays a crucial role in improving university performance outcomes by identifying strengths, enhancing them, and addressing weaknesses.The study emphasized the importance of adopting the Malcolm Baldrige model as an effective tool for evaluating university performance, contributing to the improvement of higher education quality. The research presented a set of recommendations, the most notable of which is the necessity of disseminating and adopting a culture of external auditing based on the Malcolm Baldrige model among all stakeholders in universities to evaluate university performance. This is due to its positive impact on enhancing performance quality. Additionally, the study highlighted the importance of training university leaders on the principles of transparency and accountability to enhance efficiency, achieve strategic goals, improve financial management, and reduce waste, thus enhancing universities’ economic efficiency.